Development and validation of a stability indicating isocratic HPLC method for gemcitabine with application to drug release from poly lactic‐co‐glycolic acid nanoparticles and enzymatic degradation studies. (15th September 2015) - Chen, Guanyu; Svirskis, Darren; Wen, Jingyuan
Abstract Objectives Previously reported HPLC methods for gemcitabine determination are time‐consuming with complicated mobile phases and gradient elution. Thus, a sensitive and stability‐indicating isocratic HPLC method, which provides simple, fast and precise measurements, was developed. This method was applied to study the digestive enzymatic degradation of gemcitabine, for the first time, and the protection afforded following incorporation into poly lactic‐co‐glycolic acid (PLGA) nanoparticles. Methods An analytical HPLC method was developed with an optimized combination of operating conditions. Forced degradation and application of the method to in‐vitro drug release studies were conducted. Finally, gemcitabine‐loaded nanoparticles were exposed to the digestive enzymes pepsin, trypsin and α‐chymotrypsin, and the resulting degradation evaluated. Key findings The analytical method was linear between 1 and 100 μg/ml, with excellent accuracy of 99.91–101.77% and precision of 1.71 or lower, with a 0.014 μg/ml limit of detection (LOD) and a 0.043 μg/ml limit of quantification (LOQ). Following exposure of gemcitabine to stressors, the drug was relatively stable in strong acid (1 N HCl), base (1 N NaOH) and as an aqueous solution exposed to light over 7 days, with less than 10% degradation. However, gemcitabine was more susceptible to degradation at 70°C and oxidative conditions (3% v/v H2O2) with greater than 10% degradation noted after 7 days. In‐vitro drug release studies demonstrated a sustained drug release profile from PLGA nanoparticles, which also improved the resistance of gemcitabine to enzymatic degradation. Conclusion These results demonstrate the utility and effectiveness of this simple isocratic HPLC method in evaluating the overall performance of a gemcitabine‐loaded formulation.